ADAPTIVE STRATEGIES OF TEACHING AND ASSESSMENT IN WARTIME CONDITIONS - Safronova, I. A.; Zhyr, S. I.; Verba, O. V.; Shyshkanova, G. A. (Systems and Technologies, 2025)
The modern system of higher education in Ukraine has faced unprecedented challenges due to the war. Traditional pedagogical approaches to teaching and assessment have proven ineffective amid constant psychological stress, technical disruptions, and large student cohorts. This creates an excessive workload for lecturers, making an individual approach nearly impossible. The widespread failure to meet deadlines leads to a chaotic verification process and devalues traditional control mechanisms. The purpose of this work is to analyze these problems and develop adaptive approaches to organizing the educational process that will help maintain the quality of education while minimizing the workload on lecturers. The paper proposes a rethinking of task design. Instead of a large number of lengthy assignments, it suggests focusing on 2-3 key, process-oriented tasks per semester that require knowledge integration. The importance of using group projects is also emphasized. Special attention is paid to adapting the feedback and assessment system. Instead of individual comments, minimalist and scalable feedback (e.g., a "traffic light" system, templates, general seminars) is proposed. It also considers combined verification methods that integrate automated tests with elements to prevent academic dishonesty and the misuse of AI, as well as selective oral interviews. The work also highlights the importance of fostering students' intrinsic motivation through projects with real-world application. It emphasizes the need for systematic psychological and methodological support for lecturers from the university administration, including adapting assessment requirements and providing access to modern digital tools. The conclusions underscore that the proposed solutions are effective, compromise-based strategies that help maintain the quality of education and academic integrity while minimizing the risk of professional burnout in unpredictable conditions. The results can serve as a basis for developing practical recommendations for higher education institutions operating in a crisis.